Wide‐band radar cross‐section reduction for antenna using frequency selective absorber. Issue 21 (1st October 2016) - Li, Yang; Zhang, Kunzhe; Yang, Linan; Du, Lin
Abstract : This Letter presents a new method for radar cross‐section reduction (RCSR) of patch antenna in the case of glancing incidence ( θ ≥ 70°). The reduction is realised by using frequency selective absorber which consists of lumped capacitance, inductance and resistance. Series inductances and capacitances act as frequency selectors and lumped resistances act as absorbers. By controlling the value of LRC, the circuit can only absorb the power of induced current generated by plane wave without affecting the radiation current. Considering the distribution effect of antenna, the number and position of LRC circuit must be carefully selected. Simulated and measured results show that in the case of glancing incidence, the RCS of antenna can be reduced in the angular range of −180° ≤ φ ≤ + 180° from 8 to 18 GHz. The average reduction of RCS is more than 15 dB and the maximum reduction is as far as 30 dB. Meanwhile, the gain of antenna can be well maintained.